Influence of Asset Tangibility on Financial Performance of Non-Listed Building and Construction Firms in Kenya (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Asset tangibility constitutes a fundamental determinant through which business entities secure financing and enhance their operational capacity, thus necessitating strategic management of tangible asset portfolios. The principal challenge resides in optimizing the utilization of fixed assets to generate superior financial returns while maintaining adequate collateral value for borrowing purposes. Kenya’s building and construction industry recorded performance metrics of 3.2/3.5 in third order during the 2014/2016 study period, representing a notable decline when juxtaposed against the 5.8 and 6.0 percentages achieved during 2005/2006. This suboptimal performance trajectory within the construction sector, according to extant literature, was attributable to the asset composition and utilization patterns among industry participants. This circumstance prompted the current investigation into the effect of asset tangibility on the financial performance of non-listed building and construction enterprises operating in Kenya. The research endeavor sought to assess the influence of asset tangibility ratios on profitability metrics of these non-listed construction firms. The study employed Return on Assets (ROA) and Return on Equity (ROE) as proxies for financial performance evaluation. The investigation covered the period spanning 2014 to 2016. The theoretical framework incorporated Pecking Order theory. A descriptive survey design was adopted as the research methodology. Secondary data were extracted from consolidated financial statement records maintained at the National Construction Authority and the Kenya Association of Manufacturers. The target population encompassed all 10 Tier 1 non-listed building and construction firms registered with the National Construction Authority during the three-year study window. The sample size corresponded to the entire target population, with secondary data serving as the primary information source. Analytical techniques comprised mean calculations, correlation regression modeling, and ANOVA (F-test). Findings were interpreted and presented through tabular and graphical representations, utilizing SPSS software version 2.1 for efficient data processing. The outcomes derived from this analysis demonstrated that asset tangibility exerts a discernible influence on the financial standing of non-listed building and construction firms in Kenya. The evidence indicated that financial performance tends to improve when tangible assets are effectively managed and utilized within the capital structure of the respective firm. This observation provides compelling justification for strategic investment in fixed assets as opposed to maintaining excessive liquid holdings. Proper asset management proved to enhance operational efficiency as it facilitates access to credit through collateralization while generating productive capacity that exceeds the benefits expected of holding non-productive assets. The findings of this study will enable management and financial practitioners to evaluate corporate growth characteristics, asset utilization efficiency, and financial performance metrics to project future enterprise value. The research recommends that business entities should work on optimizing asset tangibility ratios within their capital structures as a strategy for enhancing financial performance and maximizing shareholder wealth creation.